Impact of Natural Disaster Shocks on Farm Household Poverty Vulnerability—A Threshold Effect Based on Livelihood Resilience - Lu, Honggang; Zheng, Jiaxi; Ou, Hanyun; Liu, Yinong; Li, Xijian (Frontiers in Ecology and Evolution, 2022)
Disaster-related poverty poses a major challenge to poverty eradication and consolidation, while livelihood resilience is a critical component for farm households to resist hazards and escape from poverty. Using data from China Family Panel Studies, this study first investigated the impact of natural disasters on farm households' vulnerability to poverty. By taking livelihood resilience and its decomposition dimensions as thresholds, the livelihood resilience mechanism between natural disasters and poverty was investigated. The study results show that natural disaster shocks, natural disaster intensity and natural disaster frequency all had a significant positive effect on farm households’ vulnerability to poverty. The threshold test finds that natural disasters had larger effects on the poverty vulnerability of the farmers with lower buffer, self-organizing and learning capacities. When the livelihood resilience exceeded the second threshold, the effect of natural disasters on poverty vulnerability was magnified; when the livelihood resilience exceeded the third threshold, the effect of natural disasters on poverty vulnerability was magnified. Therefore, farmer resilience should be clarified from the perspective of livelihood resilience. A policy support system should be established to improve the buffer capacity, the self-organizing capacity and the learning capacity of farmers. Thus, farmers can escape from poverty and achieve long-term income growth.